Current practices and experience of transition of young people on long term home parenteral nutrition (PN) to adult services – A perspective from specialist centres. (August 2016) - Kyrana, E.; Beath, S.V.; Gabe, S.; Small, M.; Hill, S.; ,; ,
Summary: Background: There has been an estimated fivefold increase in the number of children receiving parenteral nutrition (PN) at home in the past 10 years with some children approaching the age when they should be referred to adult services whilst still on treatment. Models of care for moving young people onto adult providers of PN at home are not yet well developed, and transition is a potentially dangerous time for young people with complex health needs. Methods: A questionnaire to ascertain current experience and practices of transition in the context of home PN services was dispatched to 170 consultant gastroenterologists who were members of the British Association of Parenteral and Enteral Nutrition (BAPEN) and also to all 40 members of the Nutrition and IF working group of the British Society of Paediatric Gastroenterology and Nutrition (BSPGHAN). Anonymised returns were received from 12 adult and 18 paediatric centres. Results: We estimate about 50% paediatric IF centres, and the three largest adult IF centres responded to the survey. We identified 14 young adults already transitioned and 43 currently in transition. The practices and processes of transition reported were highly variable. Time taken to achieve transition ranged from under 6 months up to 2 years. The most frequent concerns to be identified were confusion around care routines and psychological problems at the time of transition (in one third of respondents). Conclusions: We conclude that a transition pathway and service standards for adolescents on home PN should be developed, consideration should be given to checklists for practical aspects (e.g. pumps), key worker and psychology input to enhance emotional resilience of the young people and carers.